European Security Strategy in the 21st Century: The Blair Doctrine Revisited - Balla, Evanthia (2017)
The work analyses the nature of the 2003 ESS and its 2008 review, evaluating the successes and limits of these documents, under the light of the changing European security scene. The post-9/11 political adventurisms and Blair’s doctrine serve as a guide on EU’s next steps.